2005
DOI: 10.1128/aac.49.2.836-839.2005
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination of Sulfonamide Resistance Genes ( sul1 , sul2 , and sul3 ) in Portuguese Salmonella enterica Strains and Relation with Integrons

Abstract: In 200 sulfonamide-resistant Portuguese Salmonella isolates, 152 sul1, 74 sul2, and 14 sul3 genes were detected. Class 1 integrons were always associated with sul genes, including sul3 alone in some isolates. The sul3 gene has been identified in isolates from different sources and serotypes, which also carried a class 1 integron with aadA and dfrA gene cassettes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
121
4
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(146 citation statements)
references
References 19 publications
16
121
4
5
Order By: Relevance
“…Three percent of the isolates had no detectable sul gene, 12.5% possessed two genes, and two isolates carried three genes (Table 1). Similar (2,3,14,19) or higher (4,11,17) values for multiple genes have been reported by others. The overall higher prevalence of sul1 in Salmonella isolates and of sul2 and sul3 in E. coli isolates was in agreement with the results of previous studies (2-4, 11, 12, 14, 21).…”
supporting
confidence: 62%
See 1 more Smart Citation
“…Three percent of the isolates had no detectable sul gene, 12.5% possessed two genes, and two isolates carried three genes (Table 1). Similar (2,3,14,19) or higher (4,11,17) values for multiple genes have been reported by others. The overall higher prevalence of sul1 in Salmonella isolates and of sul2 and sul3 in E. coli isolates was in agreement with the results of previous studies (2-4, 11, 12, 14, 21).…”
supporting
confidence: 62%
“…Although these isolates were not typed, previous results have shown that sul3 is present in both pathogenic and commensal porcine E. coli isolates (5) of at least 13 different serotypes (P. Boerlin and R. M. Travis, unpublished data). The sul3 gene has spread extensively across porcine E. coli populations in North America and Europe but remains uncommon in other major farm animal species and in Salmonella populations (Table 1) (2,13). It may require more time to spread to other populations.…”
Section: Ni Nimentioning
confidence: 99%
“…In this study, the trimethoprim determinant dfr (A1) gene was haboured by 5 (35.7%) of the examined isolates. This rate of trimethoprim resistance gene acquisition is high, and may be due to selection resulting from frequent use of sulfonamide/trimethoprim combination (due to its broad-spectrum activity) in small animal medicine (Antunes et al 2005, Torkan et al 2015. This reason may also explain the 28.6% prevalence of sul(1) gene in the examined isolates.…”
Section: % a A D ( A 1 ) T E T ( A ) T E T ( B ) D F R ( A 1 ) Smentioning
confidence: 83%
“…Previous investigations have screened for all three sul genes, but only Antunes et al (2), in an investigation of Salmonella enterica strains, found all three genes. One previous study screened for all three genes in environmental isolates and soil; Heuer and Smalla (13) screened silt and loamy sand soils, known to have lower sorbance properties for antibiotics (especially for tetracyclines and sulfonamides) than clay soils (8,10).…”
mentioning
confidence: 99%